2001
DOI: 10.1006/cbir.2001.0774
|View full text |Cite
|
Sign up to set email alerts
|

[Ca2+]iRISE IN JURKAT E6‐1 CELL LINES FROM DIFFERENT SOURCES AS A RESPONSE TO 50Hz MAGNETIC FIELD EXPOSURE IS A REPRODUCIBLE EFFECT AND INDEPENDENT OF POLY‐l‐LYSINE TREATMENT

Abstract: Jurkat E6-1 cells obtained from three different sources were compared with respect to intracellular calcium response to a 50 Hz, 0.15 mT, magnetic field, to treatment with poly-L-lysine and to protein expression at the cell surface. The fura-2 single cell measurements were a replication study performed by three members of our group. The cells responded to the applied magnetic fields, although the percentage of responding cells was lower than in earlier studies. The geomagnetic field was backed off without chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…It may very well be that different calcium channels are responsible for the weaker electric field effects we describe. However, there have been reports where alterations in internal calcium levels in cultured T-cell lines were seen in response to exposure to 50 Hz, 0.15 mT magnetic fields (Lindstrom et al, 1993;Mattsson et al, 2001). Interestingly, in these experiments it could not be ruled out that the effects were due to induced electric fields at or below 50 mV/m.…”
Section: Discussionmentioning
confidence: 95%
“…It may very well be that different calcium channels are responsible for the weaker electric field effects we describe. However, there have been reports where alterations in internal calcium levels in cultured T-cell lines were seen in response to exposure to 50 Hz, 0.15 mT magnetic fields (Lindstrom et al, 1993;Mattsson et al, 2001). Interestingly, in these experiments it could not be ruled out that the effects were due to induced electric fields at or below 50 mV/m.…”
Section: Discussionmentioning
confidence: 95%
“…Resting cytosolic free calcium is generally maintained at very low levels ($100 nM) [Mattsson et al, 2001] with calcium influx to the cytoplasm being controlled by a variety of Ca 2þ channels both on the plasma and intracellular membranes. An assortment of Ca 2þ channels exist on the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium ions are important second messengers involved in a number of signal transduction pathways, which include muscle contraction, secretion, neuronal excitability, metabolism, cell proliferation, and cell death. Resting cytosolic free calcium is generally maintained at very low levels ($100 nM) [Mattsson et al, 2001] with calcium influx to the cytoplasm being controlled by a variety of Ca 2þ channels both on the plasma and intracellular membranes. An assortment of Ca 2þ channels exist on the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have addressed the interaction between EMF and calcium fluxes, because calcium is a principal regulator of several cellular processes. Modulations in intracellular Ca 2+ concentrations during exposure to EMF were reported by various investigators [Liburdy et al, 1993a; Lindström et al, 1993; Löschinger et al, 1999; Mattsson et al, 2001]. It has been concluded that modulation of intracellular Ca 2+ concentrations is possible only in stimulated immune cells [Walleczek, 1992].…”
mentioning
confidence: 96%